Nectar production of quince (Cydonia oblonga Mill.) cultivars - Benedek, P.; Szabó, T.; Nyéki, J. (International Journal of Horticultural Science, 2000)
Nectar production of six quince cultivars were measured during three consecutive years. The nectar production of quince can be regarded to be small compared to other temperate zone fruit tree species since quince flowers contained 1.07 ± 0.06 mg of nectar in average. The extreme values, however, ranged between 0.1 and 7.3 mg/flower and this indicated that the nectar production was highly variable. The distribution of the nectar production was definitely skew because low values were definitely much more frequent than the highest ones. Our findings do not corroborate the earlier statements on the high sugar concentration of quince nectar. We found some 21-27% sugar in average, only. The normal distribution of the sugar concentration also indicates that the typical sugar concentration may be between 20-30%. Accordingly, the sugar concentration of quince nectar is rather low compared to other temperate zone fruit tree species (except pear). There was a significant negative correlation between the amount of nectar and its sugar concentration in quince flowers in all of the three years of the study (r= -0.51, n=37, p